Can education rescue genetic liability for cognitive decline?. (February 2015) - Cook, C. Justin; Fletcher, Jason M.
Abstract: Although there is a vast literature linking education and later health outcomes, the mechanisms underlying these associations are relatively unknown. In the spirit of some medical literature that leverages developmental abnormalities to understand mechanisms of normative functioning, we explore the ability of higher educational attainments to "rescue" biological/genetic liabilities in brain function through inheritance of a variant of the APOE gene shown to lead to cognitive decline, dementia, and Alzheimer's disease in old age. Deploying a between-sibling design that allows quasi-experimental variation in genotype and educational attainment within a standard gene–environment interaction framework, we show evidence that the genetic effects of the "risky" APOE variant on old-age cognitive decline are absent in individuals who complete college (vs. high school graduates). Auxiliary analyses suggest that the likely mechanisms of education are most consistent through changing brain processes (i.e., "how we think") and potentially building cognitive reserves, rather than alleviating old age cognitive decline through the channels of higher socioeconomic status and resources over the life course. Highlights: Provides evidence education fortifies cognition from genetic atrophy. Environment rescues individuals from harmful genetic endowment. Within-family gene–environment interaction estimation limits bias.